Benchmarking key service quality indicators in UK Employee Assistance Programme Counselling: A CORE System data profile. Issue 1 (26th February 2013) - Mellor-Clark, John; Twigg, Elspeth; Farrell, Eugene; Kinder, Andrew
Abstract: Background : Levels of psychological distress appear to be increasing in the workplace, in parallel with the growth of employee assistance programme (EAP) provision offering a range of talking treatments. However, such growth takes place in the absence of a substantive body of supporting research evidence despite a quarter of a decade of research activity. Aims : To analyse a national sample of EAP data and profile relative service quality on a set of key service indicators. Method : CORE System data profiles of over 28, 000 clients were voluntarily donated by six EAP service providers. An established benchmarking methodology was used to assess the relative quality of EAP service provision compared with published CORE System benchmarks for NHS primary care and UK higher education student counselling services. Results : High quality data profiled an EAP service clientele who were quantifiably distressed, accessed treatment quickly, with the majority completing treatment and demonstrating high rates of recovery and/or improvement relative to published benchmarks from the NHS and HE comparative sectors. Limitations of the study and implications for practice and further investigation are considered.